An analysis of the textual addition in parentheses strategy in the translation of a Quranic text / Mohammad Amin Y. H. al-Hawamdeh - Mohammad Amin Y. H., al-Hawamdeh (2017)
In light of a set of renowned theories in translation studies, text-linguistics and language communication, this study aimed at analyzing the textual addition in parentheses (TAiP) strategy as encountered in a translation of the Quranic text into English. As a case study, this translation is titled as "The Noble Quran: English Translation of the Meanings and Commentary" produced by Taqi-u Din Hilali and M. Muhsin Khan (1996); it is officially approved yet highly criticized, causing controversy worldwide due to its too many parenthetical interpolations. This analysis thoroughly addressed the TAiPs in this English version of the Quran in four aspects: the functional nature of explicitation carried by the TAiPs, the TAiPs as lexically and grammatically cohesive devices of texture, the TAiPs as factors of textuality in terms of both coherence and intentionality and the comprehensibility of a TAiP-enriched text to English readers. Methodically, the study employed a relational content-analysis approach for the first three objectives. A corpus of six small-sized Makki/Madani chapters of the Quran including a total number of 442 TAiPs was selected. For the fourth objective, a survey-analysis approach was employed. A number of 73 native- English/non-Arabic speaking persons were contacted to participate in a 2-case, selfadministered questionnaire. Each aspect of this analysis was qualitatively and quantitatively presented and discussed in search of new translational norms and in an attempt towards improving such an English translation of the Quran as the Hilali-Khan one. The TAiPs were found to be: explicitatively, of linguistically obligatory and optional or referentially pragmatic and technical types in either filling-out or specifying manners; cohesively, lexical and grammatical devices of texture—in form of recurrence, reference, substitution, ellipsis and conjunction; relationally as factors of coherence and intentionality—in form of reiteration, collocation, connotation, evocation and interpretation; and lastly, communicatively, observing or helping the TAiP-including text, to a large extent, observe the comprehensibility measures of trueness, informativeness, relevance and perspicuity. New types/subtypes of the Quranic-textoriented TAiPs—set in figures and supported by representative examples from the text and statistical accounts in form of tables and charts—were provided as much illustratively as appropriate. Eventually, an improved version of this subject English translation—in which a number of such TAiPs were either included, modified or excluded—was developed.